ASSA13-11-10 The Relationship of Metabolic Syndrome and Cardiovascular Disease and Mortality in Maintenance Hemodialysis Patients. (29th April 2013) - Ling, Yu; Han, Li; Shi-xiang, Wang
Abstract : Objective: To investigate the potential contributing effects of metabolic syndrome (MS) on cardiovascular events and mortality in maintenance hemodialysis (MHD) patients. Methods: According to the diagnostic criteria for MS set by Chinese Diabetes Society, 201 subjects undergoing MHD were assigned into MS group (n = 78) or non-MS group (n = 123), in August 2009. General and laboratory data were collected for cross-sectional analyses, and the participants were followed up for 36 months. Cardiovascular events, cause of death and time were recorded for longitudinal analyses. Results: Prevalence of MS was 38.8%. Weight, waist circumference, triglyceride, total cholesterol, low density lipoprotein, fasting glucose level, uric acid and high-sensitivity C-reactive protein were significant higher in MS group compared to non-MS group, but duration of dialysis and high-density lipoprotein were lower ( P (28/123), 10.6% (13/123), 17.1% (21/123). There was significant difference between patients with and without MS in cumulative incidence of cardiovascular events (x 2 = 7.601, P = 0.006). There was relationship between the number of metabolic syndrome parameters and cardiovascular events (r = 0.236, P = 0.001). Kaplan-Meier curves showed the relationship between two groups did not remained statistically significant in cardiovascular and all-cause mortality. Impaired glycometabolism in 5 parameters of MS was a cardiovascular mortality risk factor in MHD patients. Conclusions: The prevalence of MS is high in MHD patients. MS is a risk factor of cardiovascular events, but it is not associated with cardiovascular and all-cause 3-year mortality in patients with MHD.